1999
DOI: 10.1046/j.1570-7458.1999.00472.x
|View full text |Cite
|
Sign up to set email alerts
|

Salivation into sieve elements in relation to plant chemistry: the case of the aphid Sitobion fragariae and the wheat, Triticum aestivum

Abstract: Extended sieve element salivation (E1 waveform in the electrical penetration graph) is a characteristic activity during early sieve element punctures, particularly in resistant plants. In order to explore a chemically-mediated mechanism of resistance associated with sieve element salivation, we compared the pattern of feeding behaviour of the aphid, Sitobion fragariae (Walker), on two cultivars of the wheat Triticum aestivum L., with different concentrations of hydroxamic acids (Hx). During 24 h of electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Moreover, on leaves previously infested by heterospecific aphids, the number of probes and total duration of the pathway increased significantly. These are typical features of the behaviour of aphids feeding on resistant plants, as reported in EPG studies on aphid/plant systems (Campbell et al, 1982;van Helden & Tjallingii, 1993;Cole, 1994;Caillaud et al, 1995;Klingler et al, 1998;Ramirez & Niemeyer, 1999;Sauge et al, 2002). The modifications observed in the feeding behaviour of M. persicae tested on healthy leaves of previously infested potato plants led us to hypothesize that a mechanism of systemic resistance is induced by M. persicae and Ma.…”
Section: Discussionsupporting
confidence: 59%
“…Moreover, on leaves previously infested by heterospecific aphids, the number of probes and total duration of the pathway increased significantly. These are typical features of the behaviour of aphids feeding on resistant plants, as reported in EPG studies on aphid/plant systems (Campbell et al, 1982;van Helden & Tjallingii, 1993;Cole, 1994;Caillaud et al, 1995;Klingler et al, 1998;Ramirez & Niemeyer, 1999;Sauge et al, 2002). The modifications observed in the feeding behaviour of M. persicae tested on healthy leaves of previously infested potato plants led us to hypothesize that a mechanism of systemic resistance is induced by M. persicae and Ma.…”
Section: Discussionsupporting
confidence: 59%
“…In this study, the duration of E1 was extended on Las‐infected plants, whereas the duration of E2 was reduced. A number of studies have shown increased durations of E1 by aphids on resistant plants (van Helden & Tjallingii, 1993; Caillaud et al., 1995; Ramírez & Niemeyer, 1999; Garzo et al., 2002; Tjallingii, 2006), and Ponder et al. (2000) found that E1 of R. padi was longer on nitrogen‐deficient plants.…”
Section: Resultsmentioning
confidence: 99%
“…On unacceptable and resistant host plants, aphids tend to penetrate plant tissue (probe) more frequently and for shorter periods (McLean & Kinsey, 1968;Mesfin et al, 1995), display less phloem feeding (McLean & Kinsey, 1968;Cole et al, 1993) and more salivation (Caillaud et al, 1995;Ramı´rez & Niemeyer, 1999). The capacity of a phloem-feeder to locate a suitable sieve element within a plant as a feeding site and sustain ingestion may influence its ability to achieve peak performance.…”
Section: Introductionmentioning
confidence: 99%